Ca2+/calmodulin-dependent protein kinase II regulates the inflammatory hDPSCs dentino-differentiation via BDNF/TrkB receptor signaling - Kim, Ji Hyun; Irfan, Muhammad; Sreekumar, Sreelekshmi; Chong, Kerwin; Hong, Jin; Alapati, Satish; Chung, Seung (Frontiers in Cell and Developmental Biology, 2025)
CaMKII is a serine/threonine-specific protein kinase that plays a crucial role in normal and pathological conditions. However, limited information is available regarding the roles of CaMKII in dentinogenesis, particularly in an inflammatory context. Previously, we demonstrated the pivotal role of TrkB in inflammation-induced differentiation of hDPSCs into odontoblast-like cells. Here, we investigate the interaction between CaMKII and TrkB during hDPSCs odontogenic differentiation. hDPSCs were cultured and subjected to CaMKII knockdown using siRNA, followed by treatment with dentinogenic media. TNFα-stimulated cells were treated with CaMKII- inhibitor, -protein, or TrkB antagonist, CTX-B. Immunocytochemistry and ARS were used to visualize targeted proteins and calcium deposits. Real-time PCR detected expression levels of odontogenic and mineralization markers such as DSPP and DMP-1. Our data indicate that CaMKII inhibition enhances TrkB protein levels and promotes TNFα-induced transcriptional activation of genes associated with odontogenic differentiation. CaMKII knockdown via siRNA and pharmacological inhibition elevated DSPP and DMP-1 protein levels, whereas CaMKII overexpression suppressed their expression. Notably, treatment with TNF-α and a CaMKII inhibitor upregulated DSPP and DMP-1 expression, while co-treatment with CTX-B abolished this effect. Similarly, mRNA expression of DSPP and DMP-1 was reduced at day 10. Mineralization activity exhibited a similar pattern to the expression of these markers. Our findings unveil a novel mechanism underlying the role of CaMKII via TrkB in dentinogenesis, which is vital for the success of hDPSCs engineering strategies.